Crystal structure of native α‐l‐rhamnosidase from Aspergillus terreus. Issue 11 (2nd November 2018) - Pachl, Petr; Škerlová, Jana; Šimčíková, Daniela; Kotik, Michael; Křenková, Alena; Mader, Pavel; Brynda, Jiří; Kapešová, Jana; Křen, Vladimír; Otwinowski, Zbyszek; Řezáčová, Pavlína
Abstract : The crystal structure of α‐l ‐rhamnosidase, a biotechnologically important enzyme isolated from Aspergillus terreus, reveals its active‐site architecture, domain organization and native glycosylation. Abstract : α‐l ‐Rhamnosidases cleave terminal nonreducing α‐l ‐rhamnosyl residues from many natural rhamnoglycosides. This makes them catalysts of interest for various biotechnological applications. The X‐ray structure of the GH78 family α‐l ‐rhamnosidase from Aspergillus terreus has been determined at 1.38 Å resolution using the sulfur single‐wavelength anomalous dispersion phasing method. The protein was isolated from its natural source in the native glycosylated form, and the active site contained a glucose molecule, probably from the growth medium. In addition to its catalytic domain, the α‐l ‐rhamnosidase from A. terreus contains four accessory domains of unknown function. The structural data suggest that two of these accessory domains, E and F, might play a role in stabilizing the aglycon portion of the bound substrate.